Resolusi Konflik dalam Perubahan Dunia - Sudira, I Nyoman (UI Scholars Hub, 2017)
The world has changed speedily in the decade since the end of the Cold War. An old system has disappeared and, even though it is easy to classify what has changed, it is still not yet clear what exactly the new system has taken its place. This changing of the system has given rise to significant questions around how conflict resolution will be able to accommodate all various type and pattern of conflict and able to provide the wide array of methods used to manage and resolve it. This paper will describe two main discussions which later will describe the position of Conflict resolution perspective in order to accommodating the conflict. First part of this paper will prioritize the discussion about changes in international system and the dynamic of conflict. In the second part, discussion will focus on relations between conflict resolution and various type of conflict in the changing world.